Chinese Home-Based Cardiac Rehabilitation Model Delivered by Smartphone Interaction Improves Clinical Outcomes in Patients With Coronary Heart Disease - Ma, Jing; Ge, Cheng; Shi, Yajun; Xu, Yong; Zhao, Chenghui; Gao, Ling; Wen, Dongling; Li, Tengjing; Wang, Jinli; Yan, Sherry; Smith, Sidney C.; Chen, Yundai (Frontiers in Cardiovascular Medicine, 2021)
Purpose: We evaluated the long-term effect of a smartphone-facilitated home-based cardiac rehabilitation (HBCR) model in revascularized patients with coronary heart disease (CHD) on major adverse cardiac events (MACE), and secondary outcomes, including safety, quality of life, and physical capacity. Methods: It was a prospective observational cohort study including a total of 335 CHD patients after successful percutaneous coronary intervention (PCI) referred to the CR clinic in China between July 23, 2015 and March 1, 2018. Patients were assigned to two groups: HBCR tailored by monitoring and telecommunication via smartphone app (WeChat) (HBCR group, n = 170) or usual care (control group, n = 165), with follow-up for up to 42 months. Propensity score matching was conducted to match patients in the HBCR group with those in the control group. The patients in the HBCR group received educational materials weekly and individualized exercise prescription monthly, and the control group only received 20-min education at baseline in the CR clinic. The primary outcome was MACE, analyzed by Cox regression models. The changes in the secondary outcomes were analyzed by paired t-test among the matched cohort. Results: One hundred thirty-five HBCR patients were matched with the same number of control patients. Compared to the control group, the HBCR group had a much lower incidence of MACE (1.5 vs. 8.9%, p = 0.002), with adjusted HR = 0.21, 95% CI 0.07–0.85, and also had reduced unscheduled readmission (9.7 vs. 23.0%, p = 0.002), improved exercise capacity [maximal METs (6.2 vs. 5.1, p = 0.002)], higher Seattle Angina Questionnaire score, and better control of risk factors. Conclusions: The Chinese HBCR model using smartphone interaction is a safe and effective approach to decrease cardiovascular risks of patients with CHD and improve patients' wellness. Clinical Trial Registration:http://www.chictr.org.cn, identifier: ChiCTR1800015042.